Instrumented cervical fusion using patient specific end-plate conforming interbody devices with a micro-porous structure in nine dogs with disk-associated cervical spondylomyelopathy - Driver, Colin J.; Lopez, Victor; Walton, Ben; Jones, Dan; Fentem, Rory; Tomlinson, Andrew; Rose, Jeremy (Frontiers in Veterinary Science, 2023)
Objective: To report the medium and long-term outcome of nine dogs with disc-associated cervical spondylomyelopathy (DA-CSM), treated by instrumented interbody fusion using a custom designed end-plate conforming device that features a micro-porous structure to facilitate bone in-growth. Study Design: A retrospective clinical study. Animals: Nine medium and large breed dogs. Methods: Medical records at two institutions were reviewed between January 2020 and 2023. Following magnetic resonance imaging (MRI) diagnosis, pre-operative computed tomography (CT) scans were exported for in-silico planning. Interbody devices were designed and manufactured by selecting laser melting in titanium alloy. These were surgically implanted at 13 segments alongside mono- or bi-cortical vertebral stabilisation systems. Follow-up included neurologic scoring and CT scans post-operative, at medium-term follow up and at long-term follow-up where possible. CT-determined interbody fusion and implant subsidence was evaluated. Results: Nine dogs were diagnosed with DA-CSM between C5-C7 at a total of 13 operated segments. Medium-term follow up was obtained between 2 and 8 months post-operative (3.00  1.82 months). Neurologic scoring improved (P = 0.009) in eight of nine dogs. Distraction was significant (P < 0.001) at all segments. Fusion was evident at 12/13 segments. Subsidence was evident at 3/13 operated segments but was only considered clinically relevant in one dog that did not improve; as clinical signs were mild, revision surgery was not recommended. Long-term follow up was obtained between 9 and 33 months (14.23  8.24 months); improvement was sustained in 8 dogs. The dog that suffered worsened thoracic limb paresis at medium-term follow up was also diagnosed with immune-mediated polyarthropathy (IMPA) and was euthanased 9 months post-operative due to unacceptable side-effects of corticosteroid therapy. Conclusion: End-plate conforming interbody devices with a micro-porous structure were designed, manufactured, and successfully implanted in dog with DA-CSM. This resulted in CT-determined fusion with minimal subsidence in the majority of operated segments.